UPAYA SKRINING DINI STUNTING MELALUI PEMBERDAYAAN KADER DAN PENINGKATAN PENGETAHUAN IBU TENTANG GIZI BALITA - Nilatul Izah; Seventina Nurul Hidayah; Iroma Maulida (Universitas Indraprasta PGRI, 2021)
Stunting illustrates the chronic malnutrition status during growth and development since the beginning of life, namely during the first 1000 days of life (HPK) Growth monitoring, especially body length and / or height, should be done since the newborn to assess whether or not the child's growth is normal. Early detection of growth deviations is needed for early treatment, thus providing better results and preventing the occurrence of undesirable risks. In solving problems in the community, especially in overcoming toddlers' nutrition problems, namely the incidence of stunting in infants, the community service team provides nutrition health education for toddlers to toddlers mothers and provides training to cadres on how to conduct early screening of stunting events. Community service activities in the efforts of early screening stunting through empowering cadres and increasing knowledge of mothers in meeting the nutritional needs of children under five in Pesarean Village, Pagerbarang District, Tegal Regency. Community service is carried out within 2 days, namely on December 2, 2019, providing health education to mothers of children under five about nutrition to children under five. On 3 December 2019 health education and training activities were carried out for cadres on antopometry examinations and assessment of nutritional status of children under five. In the training, cadres were given a toddler growth and development application that could be used to detect the nutritional status of toddlers so that they could be used as an initial attempt at early screening for stunting in infants. The results of community service there is an increase in the knowledge of mothers of children under five who take part in activities especially increasing knowledge about nutrition for toddlers as an effort to prevent stunting in infants, there is an increase in knowledge and skills of cadres in conducting antopometry checks on toddlers in an effort to detect early toddlers who are stunted.